Chronic obstructive pulmonary disease (Eurasian Medical Research Periodical, 2022)
Over the past 15-20 years, there has been a significant increase in the incidence of chronic obstructive pulmonary disease (COPD) in various countries of the world. At the same time, a situation has arisen when practitioners and specialists dealing with the problem of COPD know more about how to treat this disease than about what is the point of investing in the very concept of COPD. This disease is characterized by incompletely reversible airflow limitation. This limitation is usually progressive and is associated with an abnormal reaction of the lungs to pathogenic particles and gases.